Islamic nationhood and colonial Indonesia : the umma below the winds - Laffan, Michael Francis, 1969- (SOAS/RoutledgeCurzon studies on the Middle East., 2003)
This book argues that Indonesian nationalism rested on Islamic ecumenism heightened by colonial rule and the pilgrimage.